Constrictive Pericarditis Following Correction of Partial Anomalous Pulmonary Venous Drainage. (July 2017) - Ong, Chin Siang; Shankar, Sriram; Yip, James W. L.; Tay, Edgar L. W.; Teo, Lynette L. S.; Quek, Swee Chye
We report the case of a 23-year-old man who developed constrictive pericarditis within four months after pulmonary valve replacement and repair of partial anomalous pulmonary venous connection. He had previously undergone repair of tetralogy of Fallot in infancy. After an unsuccessful trial of medical management for persistent right heart failure, magnetic resonance imaging was done, which showed a thickened pericardium. He underwent a radical pericardiectomy with a good outcome. The case is presented to illustrate a less well-recognized cause of cardiac failure following congenital cardiac surgery, which may otherwise be attributed to the failure of surgery or residual complications.